HUBUNGAN KECERDASAN EMOSIONAL DENGAN KREATIVITAS BELAJAR SISWA SEKOLAH DASAR NEGERI 37 PEKANBARU (STUDI KORELASIONAL PADA SISWA KELAS IV SEKOLAH DASAR NEGERI 37 PEKANBARU) - Ibna hafizah; Eddy Noviana; Guslinda Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is intended to know the correlatioan between Emotional Quotient (EQ) and the learning creativity of State Primary School 37 students Pekanbaru. The population in this research is around 112 students of class IV at State Primary School 37 Pekanbaru. The technique is used in this research is positive Sampling Technique. The method used is Product Correlation Moment to see the correlatioan between variable of emotional quotient and learning creativity. The technique of collecting data uses try out scale and statistic method analyses by using SPSS verse 22. Based on the result of the try out hypotheses, there is a significant correlatioan between emotional quotient and learning creativity of students at State Primary School 37 Pekanbaru. It can be known from the correlation of coefficient value about 0,448 and significant level 37,596 ) 1,97. The level of the correlatioan between coefficient determinant value is around 0,200 it means that emotional quotient gives influence around 20 % towards learning creativity students at State Primary School 37 Pekanbaru.Keywords: Emotional Quotient, learning creativity